Promoter's Liability for Neglecting Consumer Rights in Concert Ticket Exchange Mechanisms - Oktaviani, Eka Putri; Sylvana Murni Deborah Hutabarat (Fakultas Syariah INSURI Ponorogo, 2025)
The poorly managed ticket exchange process at the Seventeen's World Tour Concert in Jakarta resulted in long queues, causing material losses. This article aims to analyze the promoter's responsibility for neglecting consumer rights and review the legal measures that can be taken. The method applied in this research is a normative juridical approach, incorporating statutory and case analysis. The study relies on secondary data drawn from primary, secondary, and tertiary legal materials, which are analyzed using a qualitative approach. The findings indicated that the promoter neglected the rights to comfort, security, and safety of consumers, as stated in Article 4, point a, of the Consumer Protection Law, which can be taken to stop the event in accordance with Police Regulation Number 7 of 2023. Additionally, accountability can be held based on Article 19 of the Consumer Protection Law and Article 1365 of the Civil Code, which are supported by the theory of negligence and the GCG. Consumers have the right to claim compensation through non-litigation or litigation, although the difficulty of proving immaterial losses constrains the effectiveness of lawsuits.